Recognizing and Strengthening the Role of the Njuri Ncheke in Devolved Governance in Meru County, Kenya - Kamwaria, Alex N.; Mugwe, Rukahu W.; Kamau, John M.; Githaiga, Anne J.; Guantai, Peter M.; Makin, Kasoo R.; Choti, Charles (Journal of Educational Policy and Entrepreneurial Research (JEPER), 2015)
After fifty years of mixed fortunes in governance, Kenyans hope that the devolved system of governance as enshrined in chapter eleven of the Constitution fulfills the potential the country anticipated since independence. However, the success of devolution will not only depend on the relationship between the national government and the devolved units but will also bank on involvement of other non-state actors such as indigenous institutions of social control. The Njuri Ncheke council of elders among the Ameru community, who occupies the upper Eastern region of the country, presents such an institution. Equipped with wealth of indigenous knowledge, the Njuri Ncheke council of elders can play crucial role in the devolved government, especially in regards to conflict resolution, environmental conservation, education and development, among other roles. This paper explores some of the roles the indigenous institutions of social control, such as the Njuri Ncheke, could play in the devolved system of governance in Kenya.
Keywords: Governance; Indigenous Knowledge Systems; Njuri Ncheke